2018
DOI: 10.1080/14703297.2018.1557068
|View full text |Cite
|
Sign up to set email alerts
|

Investigating university students’ intention to use mobile learning management systems in Sweden

Abstract: This study aims to explore university students' intention to use mobile learning management systems (m-LMS) in higher education in Sweden. To address this, a research model based on the technology acceptance model (TAM) and nine research hypotheses are developed. In addition to perceived usefulness and perceived ease of use from the TAM, the research model includes academic relevance, university management support and perceived mobility value from previous literature as external variables to study the adoption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
90
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(116 citation statements)
references
References 27 publications
22
90
1
3
Order By: Relevance
“…In addition, some studies have facilitated the understanding that TAM can be the drivers that may predict behavioral intention to use m-learning [5], [32]- [36]. The success of TAM in supporting studies to predict behavioral intention to use m-LMS in learning among PSETs encourages the establishment of this study's proposed model ( Figure 1).…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 87%
See 3 more Smart Citations
“…In addition, some studies have facilitated the understanding that TAM can be the drivers that may predict behavioral intention to use m-learning [5], [32]- [36]. The success of TAM in supporting studies to predict behavioral intention to use m-LMS in learning among PSETs encourages the establishment of this study's proposed model ( Figure 1).…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 87%
“…In the context of the current study, PEU indicates the degree to which PSETs believe the use of m-LMS would be effortfree. Joo [4] reported that when m-LMS was perceived ease to use while [5] informed that no correlation emerged between PEU and PU regarding the use of m-LMS in their study. Besides, PEU was reported to be significant predicting AT [5].…”
Section: G Perceived Ease Of Use (Peu)mentioning
confidence: 95%
See 2 more Smart Citations
“…As a consequence of Davis' [11] assessment, it could be argued that successful implementation of m-learning in high schools of developing countries requires investigation of all stakeholders' attitudes. A plethora of studies has been conducted to identify factors that affect the acceptance of mobile learning [12][13][14][15]. However, a key issue is whether academics have adopted an adequately broad approach when investigating the attitudes of the main players in a high school instructional setting [16].…”
Section: Introductionmentioning
confidence: 99%